PENGARUH STRATEGI PEMBELAJARAN KOOPERATIF TGT-PUZZLE TERHADAP KECERDASAN SPASIAL-VISUAL PADA MATERI BENTUK MOLEKUL - Ah. Fathul Jadid Anshori; Kriesna Kharisma Purwanto; Rendy Priyasmika (Discovery, 2022)
Abstract: Chemistry is divided into two concepts, namely concrete and defined concepts. Geometry Molecul is one of the defined concepts because the idea is at the molecular level and is invisible to the eye. So, to understand the material molecular shape requires spatial-visual intelligence. Therefore, to determine the effect of the TGT-Puzzle cooperative learning strategy on spatial-visual intelligence on the geometry molecul, this study was conducted. The purpose of this study was to determine whether or not there was an increase in spatial-visual intelligence after being taught using the TGT-Puzzle cooperative learning strategy in class X IPA MA Hidayatul Ummah Pringgoboyo. This study uses an inferential statistical method using the paired sample t-test to determine whether or not there is an increase in visual-spatial intelligence after being taught using the TGT-Puzzle cooperative learning strategy. The analysis technique uses a paired sample t-test with a significance value (sig) < 0.05. The results of this study indicate an increase in spatial-visual intelligence scores after being taught using the TGT-Puzzle cooperative learning strategy, where if there is an increase in the category from average to high average or high average to superior. Keywords​: ​​ Visual-spatial intelligence, TGT-Puzzle cooperative learning strategy, geometry molecul.